Karakteristik Budaya Organisasi Dalam Peningkatan Kinerja Pegawai Pada Kantor Samsat Kendari - Larasati, Ida Ayu Putri; Yusuf, Muhammad; Tawai, Adrian (REZ PUBLICA, 2021)
The purpose of this study is to determine the Characteristics of Organizational Culture. The method used in this research is qualitative descriptive research method by means of observation, interviews and documentation at the Kendari City Samsat Office. The conclusion in the study is that the organizational culture characteristics in the Kendari Samsat Office still need to be improved because there are still risk-taking innovations, attention to details, orientation to benefits, Orientasi In the team that must be improved again. Then the performance of existing employees can be seen from the existence of several things, namely the quality of work, accuracy, initiative, ability and communication where it will make the people who come get better service from the performance performed by existing employees at Samsat Kendari. Its performance still needs to be improved, especially regarding the timeliness and services provided to the people of Kendari City.